The mechanical properties of nanohybrid and bulk fill posterior composites - Kamalak, Hakan; Canan, Aksu Canbay; Altin, Serdar (Scientific Publishers of India, 2018)
Objectives: The objective of this work was to investigate the structural properties, thermal conductivity, Differential Thermal Analysis (DTA), Thermo-Gravimetric analysis (TG), surface homogeneity, microhardness, X-ray analysis of nanohybrid and bulk fill composites. Methods: 108 rectangular specimens were prepared from the following composites: (Estelite Sigma Quick (ESQ), Charisma Smart (CS), 3M Espe Filtek Z 250 (EFZ) and Filtek Restorative (FR)) and subjected to various artificial aging protocols (storage in distilled water for 24 h; thermal cycling, 2 × 3000 cycles 5/55°C). The materials were light-cured for 20 s in a 2 mm × 2 mm × 6 mm teflon mould. The nanoparticles of groups were identified by FT-IR spectroscopy. Surface roughness measurements were carried out by optical microscope, the Vickers hardness number was measured with the stainless steel sheet using a micro-indentation tester (Emco Test Durascan), the heat conductivity of the samples was analyzed by the home made thermal conductivity measurement system, thermogravimetric analysis (DTG, 60-AH, Schimadzu) was used to determine the filler mass fraction. Thermogravimetric analysis was performed in argon atmosphere from 30 to 850°C. Results: It was found that the composites have multiphase component such as metallic dopant and organic binder. Conclusions: The XRD investigation showed that there was a broad halo in the pattern which indicates the organic section in the composites. We found that the temperature dependence of the thermal conductivity of the composites depended on the type of the composites, which are low enough for dental applications. The micro-hardness of the samples was analyzed and the result was compared with literature and it was found that the observed results were in agreement with literature. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Composites; FTIR; Homogeneity; Micro-hardness; Porosity; SEM-EDX; Thermogravimetric analysis